Pengaruh Harga Batubara Acua Dan Volume Penjualan Terhadap Laba Bersih - Sitorus, Resty Nurhalimah; Suhono, Suhono (Peneliti.net, 2025)
The financial performance of coal companies in Indonesia in recent years has shown interesting dynamics to analyze, especially after the COVID-19 pandemic. Fluctuations in commodity prices and sales volume have an important influence on the company's net profit, but in this study there is a phenomenon that does not work linearly and uniformly in all companies. This study examines the effect of Reference Coal Price (HBA) and sales volume on the financial performance of coal companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Using secondary data from the IDX and the Directorate General of Mineral and Coal, the research was conducted with quantitative analysis through multiple linear regression with the help of SPSS 26. The results revealed that simultaneously, HBA and sales volume had a significant effect on the company's net profit. Partially, HBA and sales volume show a positive and significant influence.